Photocatalytic Vicinal Aminopyridylation of Methyl Ketones by a Double Umpolung Strategy. Issue 40 (11th August 2020) - Im, Honggu; Choi, Wonjun; Hong, Sungwoo
Abstract: A photocatalytic double umpolung strategy for the vicinal aminopyridylation of ketones was developed using pyridinium N−N ylides. The inversion of the polarity of the pyridinium N−N ylides by single‐electron oxidation successfully enables radical‐mediated 1, 3‐dipolar cycloadditions with enolsilanes formed in situ from ketones, followed by homolytic cleavage of the N−N bond. Intriguingly, the nucleophilic amino and electrophilic pyridyl groups in the ylides can be installed at the nucleophilic α‐position and electrophilic carbonyl carbon, respectively, which are typically inaccessible by their innate polarity‐driven reactivity. This method accommodates a broad scope, and the utility was further demonstrated by the late‐stage functionalization of complex biorelevant molecules. Moreover, the strategy can be successfully applied to enamides. Abstract : A photocatalytic strategy for the vicinal aminopyridylation of ketones was developed using pyridinium N−N ylides as bifunctional reagents. Intriguingly, the synthetic advances of this approach were highlighted by the selective installation of amino and pyridyl groups into the nucleophilic α‐position and electrophilic carbonyl carbon, respectively.